How The Environment Could Teach. Louis I. Kahn’s Architecture - Rubio, Rubén García; Rinella, Tiziano Aglieri (European Scientific Journal, ESJ, 2017)
The architecture of Louis I. Kahn changed radically in the 1950s. Such was the transformation that it is difficult to find its unmistakable mark in works so different like the miesian Parasol House (1944) or the palladian Fleisher House (1959). All these differences have been widely recognized by leading architectural critics, and some of them even venture to place that process of change while he was at the American Academy in Rome between 1950 and 1951. They are absolutely right in terms of time and place. But the real question arises when it comes to establishing the reasons for such a radical change in his short stay in Rome. The answer, however, is more difficult…. The three months that Kahn spent in Rome as a Resident Architect (RAAR) were really intense. Contrarily to what one might think, he was more a college friend than a Professor. His job allowed him to travel and also encouraged him to do so, so Kahn used to do it a lot. Some of these trips were nearby, but he also made a far journey that got him to Egypt and Greece. This Mediterranean journey is also widely known because of the great drawings he made. Some architectural critics even point out that this trip may have had a potential influence on his late work. But no one has dwelt upon it so far…